Open Source Licensing: Software Freedom and Intellectual Property Law - Rosen, Lawrence (Pearson, 2004)
"I have studied Rosen's book in detail and am impressed with its scope and content. I strongly recommend it to anybody interested in the current controversies surrounding open source licensing." -John Terpstra, Samba.org; cofounder, Samba-Team "Linux and open source software have forever altered the computing landscape. The important conversations no longer revolve around the technology but rather the business and legal issues. Rosen's book is must reading for anyone using or providing open source solutions." -Stuart Open Source Development Labs A Complete Guide to the Law of Open Source for Developers, Managers, and Lawyers Now that open source software is blossoming around the world, it is crucial to understand how open source licenses work-and their solid legal foundations. Open Source Initiative general counsel Lawrence Rosen presents a plain-English guide to open source law for developers, managers, users, and lawyers. Rosen clearly explains the intellectual property laws that support open source licensing, carefully reviews today's leading licenses, and helps you make the best choices for your project or organization. Coverage includes: Explanation of why the SCO litigation and other attacks won't derail open source Dispelling the myths of open source licensing Intellectual property law for nonlawyers: ownership and licensing of copyrights, patents, and trademarks "Academic licenses": BSD, MIT, Apache, and beyond The "reciprocal bargain" at the heart of the GPL Alternative licenses: Mozilla, CPL, OSL and AFL Benefits of open source, and the obligations and risks facing businesses that deploy open source software Choosing the right license: considering business models, product architecture, IP ownership, license compatibility issues, relicensing, and more Enforcing the terms and conditions of open source licenses Shared source, eventual source, and other alternative models to open source Protecting yourself against lawsuits.